Mindfulness Sebagai Terapi yang Efektif untuk Meningkatkan Kualitas Hidup Pasien dengan Coronary Artery Disease - Silaban, Anna Ria; Nurachmah, Elly; Yona, Sri (FORIKES, 2024)
There are various risk factors for coronary heart disease, one of which is psychological factors, such as: stress, anxiety, depression to loneliness; which can affect the patient's quality of life and life satisfaction. One therapy that can equip patients with the ability to overcome these problems is mindfulness. This study aimed to determine the effectiveness of mindfulness therapy to improve the quality of life of patients with coronary artery disease. This study was a systematic review with the